How do ectotherms perform in cold environments? Physiological and life-history traits in an Andean viviparous lizard - Clavijo-Baquet, Sabrina; Orellana, María J.; Sabat, Pablo; Bozinovic, Francisco (Frontiers in Ecology and Evolution, 2022)
Both the mean and the variation in environmental temperature are increasing globally. Indeed, predicted increases in temperature range from 2 to 4 ºC in the next fifty years. Ectotherms control body temperature by means of behavior selecting microsites with different temperatures, what make them more susceptible to climate change. Nevertheless, lizards living in high mountain environments have developed several mechanisms to inhabit and colonize variable environments with extreme temperatures. These mechanisms include high metabolism to be active at lower temperatures and viviparity to improve embryonic development. Despite behavioral thermoregulation may be acting as a buffer to changes in environmental temperature, other traits such as life history traits may be less flexible. Consequently, in an attempt to understand how lizards cope with harsh habitats, we evaluated some physiological traits and responses of females of Liolaemus belli from two contrasting slope sites with differences in environmental temperature and humidity, but at the same altitude in the southern Andes range. We collected pregnant females from opposite slopes and maintained them until parturition in a common-garden experiment. Females from the south-facing slope (S-slope) had higher Tpref values before and after parturition, and exhibited higher daily energy expenditure before parturition. Nevertheless, no difference in Tpref was shown by their offspring, suggesting a developmental plastic response or adaptation to lower environmental temperature. For instance, the higher metabolism during pregnancy could be associated with a shorter activity period on the snowy S-slope. Additionally, females from the S-slope had larger kidneys and gave birth later than N-slope females, likely due to developmental plasticity or genetic differentiation. How fixed are these traits on individuals from the contrasting slopes will determine the response capacity of L. belli population to climate change.